Stealing home - Torres, J., 1969- (Kids Can Press, 2021)
"Sandy Saito looks back to his childhood in 1940s Vancouver, when he was eight years old. He's a happy kid: he goes to school, reads comic books and is obsessed with baseball--especially the Asahi baseball team, the pride of the Japanese-Canadian community. Then the Japanese bomb Pearl Harbor--and everything changes. The kids Sandy used to play with every day now call him names and chase him from the playground. He and his family are no longer permitted to go outside at night or visit certain areas of the city. Japanese-Canadians are stripped of their rights, their jobs and their homes, and soon the government begins to round up Japanese families, sending them to internment camps. It isn't long before Sandy's family is among them"--